Interactive Learning Media for Mastering Lampung Language Vocabulary in 4th-5th Grade Elementary School Using the ADDIE Model - Haryuning Tias; Usep Saprudin (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The teaching of the Lampung language at the elementary school level continues to encounter significant obstacles, particularly the limited ability of students to master vocabulary due to teaching methods that lack dynamism and interactivity. This research aims to develop an interactive learning media application to enhance the daily vocabulary proficiency in the Lampung language among fourth and fifth-grade students at SD Negeri 1 Surabaya Udik. The application was developed using the ADDIE model, which encompasses five key stages—analysis, design, development, implementation, and evaluation—as a framework for instructional system design. It incorporates interactive features such as learning materials, educational videos, quizzes, and digital exercises, accessible across various devices. Findings reveal that the use of this interactive learning application significantly boosts students’ engagement and enthusiasm for learning the Lampung language, while also facilitating a more effective grasp of vocabulary. The application’s impact was assessed through a pre-test and post-test method applied to fourth and fifth-grade students, demonstrating a marked improvement in vocabulary mastery compared to traditional teaching approaches. This study adopts a quasi-experimental approach with a pre-test and post-test design without a comparison group, testing students before and after using the application. The application is anticipated to serve as a novel solution in supporting the preservation of regional languages through a technology-driven learning strategy.